Wirelessly Powered 3D Printed Hierarchical Biohybrid Robots with Multiscale Mechanical Properties (Adv. Funct. Mater. 31/2022). (1st August 2022) - Tetsuka, Hiroyuki; Pirrami, Lorenzo; Wang, Ting; Demarchi, Danilo; Shin, Su Ryon
Abstract : Biohybrid Soft Robots In article number 2202674, Su Ryon Shin and co‐workers demonstrate untethered biohybrid soft robots comprised of human cardiac muscle actuators and wirelessly powered bioelectronics that allows for electrically controlled movement without the need for batteries and wires. The direct and seamless integration strategy herein introduced will enable the full hybridization of bioelectronics with living tissues.